2018
DOI: 10.1177/0306396818793582
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a name? ‘Refugees’, ‘migrants’ and the politics of labelling

Abstract: Through a critical examination of European immigration policy and using the case of Afghan asylum seekers in the European continent, this article argues that the politics of labelling and the criminalisation and securitisation of migration undermine the protection framework for the globally displaced. However, the issue goes deeper than state politicking to circumvent responsibilities under international law. The construction of migrants as victims at best, and as cultural and security threats at worst, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 32 publications
0
43
0
3
Order By: Relevance
“…Such a narrow understanding of the status of refugee reflects contemporary EU policies, which are discouraging granting of asylum to Afghans, especially during the context of the 'crisis' (Sajjad, 2018), as well as relevant media definitions of who counts as a refugee. As visibility of refugees in the media has been low, if non-existent, before 2015, the issue has been almost exclusively linked in public discourse to the Syrian civil war.…”
Section: (Fg3 Male Professionals)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a narrow understanding of the status of refugee reflects contemporary EU policies, which are discouraging granting of asylum to Afghans, especially during the context of the 'crisis' (Sajjad, 2018), as well as relevant media definitions of who counts as a refugee. As visibility of refugees in the media has been low, if non-existent, before 2015, the issue has been almost exclusively linked in public discourse to the Syrian civil war.…”
Section: (Fg3 Male Professionals)mentioning
confidence: 99%
“…Afghans were constructed as immigrants, and by extension undeserving of hospitality, in most discussions, despite being the second refugee population in the world and the deteriorating security conditions in the country being acknowledged by UNHCR as grounds for driving people from their homes (UNHCR, 2018). Such a narrow understanding of the status of refugee reflects contemporary EU policies, which are discouraging granting of asylum to Afghans, especially during the context of the ‘crisis’ (Sajjad, 2018), as well as relevant media definitions of who counts as a refugee. As visibility of refugees in the media has been low, if non-existent, before 2015, the issue has been almost exclusively linked in public discourse to the Syrian civil war.…”
Section: The Politics Of Labelling: ‘Refugees’ Versus ‘Migrants’mentioning
confidence: 99%
“…19 In Europe, since 2015 Afghans have been one of the biggest groups to apply for asylum. 20 However, Afghans are increasingly met with the rejection of asylum claims, detention, abandonment and deportation. 21 The chances of getting asylum for Afghans in Europe have been lowered remarkably over recent years – from 68 per cent getting accepted in September 2015 to 33 per cent in December 2016.…”
Section: Afghanistan War and The Danish Deportation Regimementioning
confidence: 99%
“…After the beginning of the Syrian civil war and a huge flow of refugees in Europe since 2011 most studies [14,15] confirmed that negative attitudes towards refugees has become a prominent feature in many Western countries, whereas refugees are condemned, demonized and considered as the main object of discrimination. Research shows that their identity remains highly differentiated and controversial, which is related to the politics of labelling [16]. Currently, refugees are not only the main focus of the media but also the main players, which means that their identity is closely linked to different forms of representation.…”
Section: Social Sciencementioning
confidence: 99%